Stress responses and epigenomic instability mark the loss of somatic embryogenesis competence in grapevine. Issue 1 (2nd November 2021) - Dal Santo, Silvia; De Paoli, Emanuele; Pagliarani, Chiara; Amato, Alessandra; Celii, Mirko; Boccacci, Paolo; Zenoni, Sara; Gambino, Giorgio; Perrone, Irene
Abstract: Somatic embryogenesis (SE) represents the most appropriate tool for next-generation breeding methods in woody plants such as grapevine ( Vitis vinifera L.). However, in this species, the SE competence is strongly genotype-dependent and the molecular basis of this phenomenon is poorly understood. We explored the genetic and epigenetic basis of SE in grapevine by profiling the transcriptome, epigenome, and small RNAome of undifferentiated, embryogenic, and non-embryogenic callus tissues derived from two genotypes differing in competence for SE, Sangiovese and Cabernet Sauvignon. During the successful formation of embryonic callus, we observed the upregulation of epigenetic-related transcripts and short interfering RNAs in association with DNA hypermethylation at transposable elements in both varieties. Nevertheless, the switch to nonembryonic development matched the incomplete reinforcement of transposon silencing, and the evidence of such effect was more apparent in the recalcitrant Cabernet Sauvignon. Transcriptomic differences between the two genotypes were maximized already at early stage of culture where the recalcitrant variety expressed a broad panel of genes related to stress responses and secondary metabolism. Our data provide a different angle on the SE molecular dynamics that can be exploited to leverage SE as a biotechnological tool for fruit crop breeding. Abstract : Stress responses and incomplete reinforcement of transposon silencing shape divergent developmental routes in two grapevine cultivars with different somatic embryogenesis competence.